2015
DOI: 10.1111/gwao.12076
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Employment as a Strategy for Dealing with the Competing Demands of Work and Family? The Importance of Family/Lifestyle Motives

Abstract: In this paper, we test the argument that self‐employment may be a strategy for dealing with competing demands of work and family. We do this by comparing work–family conflict experienced by self‐employed and employed men and women. By examining to what extent the self‐employed versus regularly employed value time for themselves and their family — i.e., whether they are driven by family/lifestyle motives in their working life — we examine whether self‐employment can help reduce work–family conflict among those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 36 publications
2
34
1
3
Order By: Relevance
“…This type of employment may reduce the imbalance between work and family life because it creates opportunities for flexible scheduling and enables one to work from home (Bunk, Dugan, D'Agostino, & Barnes-Farrell, 2012;Hilbrecht & Lero, 2014). However, a recent Swedish study indicated that self-employed men and women, especially those with employees, generally experience more conflict between work and family than do employees (Johansson Sevä & Ö un, 2015). In general, this study did not find any substantial gender differences regarding the experience of conflict between work and family.…”
Section: Time Strain In Relation To Work-life Balancecontrasting
confidence: 58%
“…This type of employment may reduce the imbalance between work and family life because it creates opportunities for flexible scheduling and enables one to work from home (Bunk, Dugan, D'Agostino, & Barnes-Farrell, 2012;Hilbrecht & Lero, 2014). However, a recent Swedish study indicated that self-employed men and women, especially those with employees, generally experience more conflict between work and family than do employees (Johansson Sevä & Ö un, 2015). In general, this study did not find any substantial gender differences regarding the experience of conflict between work and family.…”
Section: Time Strain In Relation To Work-life Balancecontrasting
confidence: 58%
“…While gender did not emerge as significant in both Meager, Bates, and Cowling's (2003) and Muraina et al 's (2012) research, a substantial body of research demonstrates that gender has a powerful influence on entrepreneurship (Johansen 2013). Women often have very different aspirations for their businesses than men, often due to family roles and responsibilities (Walker and Webster 2007;Nordenmark, Vinberg, and Strandh 2012;Johansson Sevä and Öun 2015). For example, women may want a stable, small business, enabling balance between their home and working lives and flowing from their beliefs and values (Green and Cohen 1995;Marler and Moen 2005;Bunk et al 2012;Hilbrecht and Lero 2014;Bögenhold and Klinglmair 2015); perhaps explaining Elam's finding (2014) that women are less likely to start businesses and, when they do, start very different businesses to men.…”
Section: Enterprise and Gendermentioning
confidence: 99%
“…Two recent papers for Norway and Sweden also find a positive correlation between the presence of young children in the household and self-employment entry (Rønsen 2014;Andersson Joona 2017)-this in spite of the existence of family-friendly policies that encourage labor force participation among mothers and fathers with young children. However, one difference found between Sweden and Anglo-Saxon countries is that self-employed women in Sweden spend more, or as much, time on market work as wage-earning women, while the opposite is true in many other countries (Gimenez-Nadal et al 2012;Gurley-Calvez et al 2009;Mångs 2013;Johansson Sevä and Öun 2015).…”
Section: Introductionmentioning
confidence: 99%